Cattaneo-Christov model for radiative heat transfer of magnetohydrodynamic Casson-ferrofluid: A numerical study - Ali, M.E.; Sandeep, N. (Results in physics, 2017)
The knowledge of heat transfer in MHD nanofluid flows over different geometries is very important for heat exchangers design, transpiration, fiber coating, etc. Recent days, heat transfer of non-Newtonian nanofluids plays a major role in manufacturing processes due to its shear thinning and thickening properties. Naturally, magnetite (Fe3O4) nanoparticles move randomly within the base fluid. By applying the transverse magnetic field, the motion of those nanoparticles becomes uniform. This phenomenon is very useful in heat transfer processes. With this initiation, a mathematical model is developed to investigate the heat transfer behaviour of electrically conducting MHD flow of a Casson nanofluid over a cone, wedge and a plate. We consider a Cattaneo-Christov heat flux model with variable source/sink and nonlinear radiation effects. We also considered water as the base fluid suspended with magnetite nanoparticles. R-K-Felhberg-integration scheme is employed to resolve the altered governing nonlinear equations. Impacts of governing parameters on common profiles (temperature and velocity) are conversed (in three cases). By viewing the same parameters, the friction factor coefficient and heat transfer rate are discussed with the assistance of tables. It is found that the boundary layers (thermal and flow) over three geometries (cone, wedge and a plate) are not uniform. It is also found that the thermal relaxation parameter effectively enhances the heat local Nusselt number and the heat transfer performance is high in the flow over a wedge when compared with the flows over a cone and plate.